The Intricate Diagnostic Journey of a Breast Cancer Patient, Revealing Extensive Hepatic Metastasis Through Extraosseous Uptake in Planar Bone Scintigraphy and SPECT-CT Precision Mapping (Bangladesh Journal of Nuclear Medicine, 2024)
In breast cancer patients, planar bone scintigraphy is commonly used for  detecting osseous metastasis. This case report emphasizes the importance  of recognizing unusual extraosseous uptake in  bone scintigraphy, even  when negative for osteoblastic lesions. A 35-year-old post-treatment breast  carcinoma  patient exhibited unexpected radiotracer uptake in the upper  abdomen. Subsequent SPECT/CT revealed radiotracer-avid calcified  hepatic lesions and extensive non-avid metastatic lesions, however no  osteoblastic metastasis. Ultrasound-guided core  biopsy confirmed  extensive hepatic metastases secondary to ductal carcinoma of the breast.  This highlights the critical role of SPECT/CT in precisely identifying and  characterizing  lesions,  aiding in  advanced  breast  cancer diagnosis  and  management planning.Bangladesh J. Nuclear Med. 27(1): 121-126, 2024